Students' Competence in Using Participle Verbs at English Education Department of Universitas Muhammadiyah Sorong - Saputra, Dian; Rullu, St. Marhana; Yulianingsih, Lilik; Wael, Ahmad; Ohorella, Hayat M. (English Education Study Program, 2024)
This research pointed to investigate the competence of third-semester English Language Education students at Universitas Muhammadiyah Sorong (Academic Year 2022-2023) in using participle verbs. Employing a descriptive quantitative method, the research focused on a purposive sample of 20 students. The analysis revealed that the students’ competence in using participle verbs fell within the “fair” category, with an average score of 72.55. This suggests that while their ability is not exceptional, it also is not particularly weak. However, it is important to note that achieving a fair level of competence indicates a basic understanding of participle usage, but there is room for improvement. This finding underscores the need for targeted interventions and additional practice to enhance students’ proficiency in using participle verbs effectively. Based on the findings of this study, it is recommended that educational institutions implement targeted interventions to improve students' proficiency in using participle verbs effectively. These interventions could include specialized grammar workshops, additional practice sessions.